2016
DOI: 10.1002/mren.201600046
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Deactivation of Phillips Catalyst for Ethylene Polymerization Using Various Activators

Abstract: The present article reveals important roles of metal alkyl activators in tuning the performance of the Phillips catalyst in ethylene polymerization. The addition of aluminum alkyl aids the activation of the catalyst, while excess addition leads to the loss of the activity. The balance between the activation and deactivation depends on the type of employed aluminum alkyl, and tri‐n‐octylaluminum offers the most efficient catalyst usage by preferentially suppressing the deactivation. The passivation of aluminum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 32 publications
4
13
0
Order By: Relevance
“…Figure ). It is obvious that all the catalysts show an optimum Al/V at which the maximum activity is reached, as the cocatalysts act as alkylation reagent for active centers and scavenger for reaction system, but overdose of cocatalyst would result in deactivation through overreduction of the active centers . The optimum Al/V for VO x /SiO 2 –Al 2 O 3 –SO 4 2− , VO x /SiO 2 –ZrO 2 –SO 4 2− and VO x /SiO 2 –TiO 2 –SO 4 2− are 60, 60, and 70, respectively, and the maximum activity is similar for each catalyst at 2200 kg PE mol −1 V, which is equal to or lower than the activity of some supported V‐based Ziegler‐Natta catalysts, but is definitely higher than that of VO x /SiO 2 –MO y (M = Al, Zr, or Ti) at 1200 kg PE mol −1 V .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure ). It is obvious that all the catalysts show an optimum Al/V at which the maximum activity is reached, as the cocatalysts act as alkylation reagent for active centers and scavenger for reaction system, but overdose of cocatalyst would result in deactivation through overreduction of the active centers . The optimum Al/V for VO x /SiO 2 –Al 2 O 3 –SO 4 2− , VO x /SiO 2 –ZrO 2 –SO 4 2− and VO x /SiO 2 –TiO 2 –SO 4 2− are 60, 60, and 70, respectively, and the maximum activity is similar for each catalyst at 2200 kg PE mol −1 V, which is equal to or lower than the activity of some supported V‐based Ziegler‐Natta catalysts, but is definitely higher than that of VO x /SiO 2 –MO y (M = Al, Zr, or Ti) at 1200 kg PE mol −1 V .…”
Section: Resultsmentioning
confidence: 99%
“…It is obvious that all the catalysts show an optimum Al/V at which the maximum activity is reached, as the cocatalysts act as alkylation reagent for active centers and scavenger for reaction system, but overdose of cocatalyst would result in deactivation through overreduction of the active centers. [36] The optimum Al 4 2− and VO x /SiO 2 -TiO 2 -SO 4 2− are 60, 60, and 70, respectively, and the maximum activity is similar for each catalyst at 2200 kg PE mol −1 V, which is equal to or lower than the activity of some supported V-based Ziegler-Natta catalysts, but is definitely higher than that of VO x /SiO 2 -MO y (M = Al, Zr, or Ti) at 1200 kg PE mol −1 V. [22,37,38] This confirms that the sulfation indeed helps to improve the activity of the vanadium-oxide-based catalysts for ethylene polymerization. The PEs synthesized under the given conditions have M v about 3 × 10 6 g mol −1 , which is definitely above the critical value for UHMWPE (see Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…[6,7] The added alkyl aluminum can also improve the hydrogen response of Phillips Cr-based catalyst in the ethylene polymerization, while the original catalyst is not sensitive to hydrogen as a chain transfer agent. [8] S-2 catalyst used in the UNIPOL gas phase process is pretreated with alkyl aluminum, which is called the prereduction process. [9,10] There are several patent literature about the prereduction step of alkyl aluminum in the preparation of catalyst.…”
Section: Effects Of Alkyl Aluminum On Sio 2 -Supported Silyl-chromatementioning
confidence: 99%
“…It was reported that with the addition of alkyl aluminum, a chain growth initiator of chromium‐alkyl species could be formed during polymerization and the frequency of long chain branches in polyethylene was improved as a result of enhanced active site densities . The added alkyl aluminum can also improve the hydrogen response of Phillips Cr‐based catalyst in the ethylene polymerization, while the original catalyst is not sensitive to hydrogen as a chain transfer agent …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation